On Quotient KS-semigroups Induced by Fuzzy KS-ideals (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce some types of fuzzy ideals on KS-semigroups, compare their relationships with the existing fuzzy KS-ideals and investigate their properties. We discuss the construction of quotient KS-semigroups induced by fuzzy KS-ideals, show that this quotient structure is a generalization of the existing quotient structure and prove properties of this generalized structure. Moreover, we investigate the quotient structure of product KS-semigroups via fuzzy KS-ideals.
Keywords: quotient KS-semigroups; congruence relation; fuzzy KS-ideals; fuzzy KS-p-ideals; fuzzy (commutative, implicative) KS-ideals